EVENT STUDY: THE IMPACT OF THE RUSSIA-UKRAINE INVASION ON STOCK PRICES AND ABNORMAL RETURNS - Widoretno, Astrini Aning; Fitriyah, Ni'mah Nur Aida (Universitas Bunda Mulia, 2024)
Background of The Study: The capital market is able to react quickly to issues that arise around it. In February 2022, Russia conducted military operations against Ukraine. Of course, this stole global attention. Investors need to pay attention to any information that may affect trading in the capital market.Purpose of The Study: Empirically analyze how the news of Russia's invasion of Ukraine affects the stock prices and abnormal returns of energy industry companies listed on the Indonesia Stock Exchange (IDX).Research Method: The research uses the event study method, with an observation period of 30 days before and after the announcement to measure the public reaction to the news of the invasion by Russia.Research Result: The results showed that there were visible changes in stock prices from before to after the news of the Russia-Ukraine invasion was announced, as shown in this study. Meanwhile, there is no visible difference in abnormal returns either before or after the news announcement of the invasion between Russia and Ukraine is published.Research Gap: Russia's invasion of Ukraine occurred in 2022, and this study examines companies in the energy industry.Keywords: Russia-Ukraine Invasion, Stock Price, Abnormal Return, Event Study.